Differential mRNA expression of inflammasome genes NLRP1 and NLRP3 in abdominal aneurysmal and occlusive aortic disease. (April 2018) - Gonzalez-Hidalgo, Carmen; De Haro, Joaquin; Bleda, Silvia; Cañibano, Cristina; Michel, Ignacio; Acin, Francisco
NLRP1 and NLRP3 inflammasomes might differentially mediate the chronic inflammatory response in abdominal aortic aneurysm (AAA) and aortic occlusive disease (AOD). We measure differential relative gene expression of NLRP1 and NLRP3 inflammasomes in aortic tissues from 30 patients undergoing AAA open repair compared to aortic biopsies from 30 patients undergoing surgery to treat AOD. Aortic wall samples from autopsy without aortic disease were used as controls. NLRP3 was overexpressed in patients with AAA and AOD (RQ 1.185 ± 0.15, and 1.098 ± 0.05, respectively) compared to donors (RQ 1.001 ± 0.08) (OR 2.8, 95% CI 1.2–4.3, p < 0.05 for AAA and OR 2.1, 95% CI 1.1–3.8, p < 0.05 for AOD). NLRP1 gene expression was significantly upregulated in patients with AOD (RQ 1.197 ± 0.09). Meanwhile, NLRP1 was normal expressed in AAA (RQ 1.003 ± 0.07) as well as in autopsy aortic specimens (RQ 1.005 ± 0.11). Enhanced NLRP1 expression in AOD was even significant when compared to AAA (OR 2.3, 95% CI 1.2–3.3, p < 0.05) or controls (OR 2.2, 95% CI 1.1–3.1, p < 0.05). According to our findings, NLRP3 could be involved in the common etiology of AAA and AOD, whereas NLRP1 appears to have a specific role in AOD development.